Cinema e democracia cultural na periferia de Araraquara - Brizolari, Ana Carolina [UNESP]; Simis, Anita [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This project will address the issue of cultural democracy , that is, the right to access all cultural manifestations by all social classes , which in theory should be easy to access to the entire population , but in practice it is still very difficult to achieve , affecting mainly those less fortunate. Combining public inclusion policies, the main objective will be to spread the cinema, in the context of cultural practices in the most distant places,which are the outskirts of Araraquara, analysing mainly the specific groups and their necessities, which will provide a new form of learning based on cultural practice of cinema.

Neste projeto abordaremos a problemática da democracia cultural, isto é, o direito de acesso à todas as manifestações culturais por todas as classes sociais, que em teoria deveria ser de fácil acesso para toda a população, porém na prática ainda é muito difícil de ser concretizar, prejudicando principalmente aqueles menos favorecidos. Aliando políticas públicas de inserção, o objetivo central será difundir o cinema, no âmbito das práticas culturais nos locais mais longínquos, no caso as periferias da cidade de Araraquara, analisando principalmente os públicos específicos e suas necessidades, o que possibilitará propor uma nova forma de aprendizagem baseada na prática cultural do cinema.
Keywords: Cinema; Suburbs; Culture; Cinema; Periferia; Cultura